1995
DOI: 10.1063/1.113483
|View full text |Cite
|
Sign up to set email alerts
|

Bias-enhanced nucleation of highly oriented diamond on titanium carbide (111) substrates

Abstract: The bias-enhanced nucleation (BEN) technique has been applied to TiC(111) substrates and resulted in deposition of oriented diamond particles. The orientation was observed via scanning electron microscopy. A dense region of oriented particles was not observed on the samples, presumably due to the excessive twinning of the diamond. However, micrographs taken throughout the substrate showed diamond particles having similar orientation with respect to each other. Some of the diamond particles showed evidence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The oriented and heteroepitaxial diamond growth is exemplified by such different materials as sapphire [69], Co [70], Pt [71], TiC [72], graphite [73], BeO [74], Ni 3 Ge [75], and Re [76], which are not discussed below. Detailed reviews of the synthesis of heteroepitaxial and textured diamond films can be found in monographs [2,6,49].…”
Section: Textured and Heteroepitaxial Diamond Filmsmentioning
confidence: 99%
“…The oriented and heteroepitaxial diamond growth is exemplified by such different materials as sapphire [69], Co [70], Pt [71], TiC [72], graphite [73], BeO [74], Ni 3 Ge [75], and Re [76], which are not discussed below. Detailed reviews of the synthesis of heteroepitaxial and textured diamond films can be found in monographs [2,6,49].…”
Section: Textured and Heteroepitaxial Diamond Filmsmentioning
confidence: 99%
“…The unique properties of diamond make it an ideal material for a wide range of scientific and technological applications such as optics, microelectronics, tribological, thermal management, biomedical, DNA sensor, and so on. [1][2][3][4][5][6] Recently, diamond deposition on the nondiamond substrates is performed by nucleation processing step. Nucleation, corresponds to the formation of diamond nuclei, i.e., the smallest thermodynamically stable island, at the substrate surface.…”
Section: Introductionmentioning
confidence: 99%
“…The exceptional physical and chemical properties of diamond such as wide band gap, chemical inertness, high carrier mobility, excellent biological compatibility, high propagation speed of acoustic wave, good optical transparency, high thermal conductivity and the greatest hardness that make its use advantageous in a wide range of applications [5][6][7]. Several methods have been proposed for the synthesis of high crystalline diamond films by microwave plasma chemical vapor deposition (MPCVD) at high temperature and pressure [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%